Dampak Faktor Pelayanan Terhadap Tingkat Kepuasan Konsumen Pada PT. Mandiri Axa General Insurance Cabang Surabaya : Study kasus Di PT. Mandiri Axa - Achmad Faudji; I Gede Wiyase (Journal of Management and Creative Business, 2024)
With the increasing progress and development of technology and science, followed by increasing patterns of people's lives, this has resulted in increasingly diverse needs in society. The high per capita income of the population means that people have assets that require safety protection from the threat of danger, therefore insurance contracts are very important for the community. This research aims to determine the influence of service factors on the level of consumer satisfaction at PT. Mandiri AXA General Insurance Surabaya Branch. The analytical method used is Partial Least Square (PLS) which is followed by hypothesis testing, where the data used is a sample of 50 customers at PT. Mandiri AXA General Insurance. The conclusion obtained from this research is that the better the service provided, the higher the level of consumer satisfaction (customers) of PT. Mandiri AXA General Insurance.